2016
DOI: 10.1158/1078-0432.ccr-16-0124
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Inhibition of RNA Pol I Transcription and PIM Kinase as a New Therapeutic Approach to Treat Advanced Prostate Cancer

Abstract: Our results demonstrate preclinical efficacy of targeting the ribosome at multiple levels and provide a new approach for the treatment of prostate cancer. Clin Cancer Res; 22(22); 5539-52. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 48 publications
(64 reference statements)
3
61
0
Order By: Relevance
“…The concept of a ceiling on the nuclear DNA/cytoplasm volume relationship is not unique to skeletal muscle and is actually a primary driver of cell division in mitotically active mononucleated cells. In fact, some current strategies in cancer-targeting therapeutics are focused on disrupting the protein synthetic machinery in cancer cells to limit cellular hypertrophy, thereby mitigating proliferation (Devlin et al 2016; Rebello et al 2016). …”
Section: Muscle Stem (Satellite) Cell Activitymentioning
confidence: 99%
“…The concept of a ceiling on the nuclear DNA/cytoplasm volume relationship is not unique to skeletal muscle and is actually a primary driver of cell division in mitotically active mononucleated cells. In fact, some current strategies in cancer-targeting therapeutics are focused on disrupting the protein synthetic machinery in cancer cells to limit cellular hypertrophy, thereby mitigating proliferation (Devlin et al 2016; Rebello et al 2016). …”
Section: Muscle Stem (Satellite) Cell Activitymentioning
confidence: 99%
“…However, such studies are now being extended to various solid organ malignancies including metastatic/recurrent/locally advanced/unresectable triple negative breast cancer which is currently recruiting through the Canadian Cancer Trials group (NCT02719977). This is a logical extension as there is preliminary data for efficacy of CX-5461 in solid tumours, with pre-clinical data suggesting a role in prostate cancer[14]. Similarly, studies in PDAC cell lines have also shown promise[76], as documented by Drygin et al[76] using MIA PaCa-2 cell lines.…”
Section: Ribosome Biogenesismentioning
confidence: 97%
“…To this end, novel approaches that are non, or at least minimally genotoxic are of particular interest. The potential advantages observed with targeted therapies in reducing systemic side effects and improving outcomes for other malignancies have gained interest in the realm of PDAC and will be briefly discussed in this review with a particular focus on the emerging role of nucleolar stress pathway and ribosome biogenesis as a potential treatment option given its promising results in the management of haematological malignancies and prostate cancer[12-14]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rebello et al [167] reported the efficacy of a combination of RNA polymerase I (Rpol I) and proto-oncogene serine/threonine-protein (PIM) kinase inhibitors (CX-5461 and CX-6258) for MYC-driven prostate cancer. They showed that c-MYC is related to both Rpol I and PIM kinase activation, which were significantly inhibited by both drugs in Hi-MYC mice [167]. …”
Section: Development Of Novel Drugsmentioning
confidence: 99%